(untitled) (European Journal of Interdisciplinary Studies, 2015)
Development of policies for the prevention of every nature of organized crime from the security institutions of the Republic of Kosovo is an important element through which is aimed the coordination of works and prevention activities in order to respond to negative phenomena through taking precautions. Prevention means all activities that impact on halting and reducing crime as a social phenomenon, both quantitatively as well as qualitatively, through occasional initiatives (ad hoc). Advancing capacity to prevent crime is the need of the time and the challenge faced by the countries of the Western Balkans, especially Kosovo, because in this area there is still the old belief that only the police should be involved to prevent and fight trafficking of human beings. Nature and trends of trafficking of human beings have taken a direction in which the police as law enforcement agency cannot as such prevent these crime phenomena. Therefore, it is time imperative that in the field of crime prevention of human trafficking engage all relevant institutions with special emphasis on civil society and community in particular. To cope with the challenges of preventing and fighting trafficking of human beings, activities within state’s territory are not sufficient, but it is vital that states align and coordinate activities at the regional level in real time, place and space identified for common actions. This paper aims to address this phenomenon not only in the case of Kosovo, but also in the Western Balkan region. The main thesis of this paper is the articulation of the problem in order to successfully prevent the phenomenon of trafficking of human beings through awareness of citizens, while from institutions is required opening of perspectives for new generations, for work and life, through economic development, fighting poverty, stimulating employment and preventing the migration in different countries. To successfully prevent crime, particularly trafficking in human beings, it is necessary that responsible institutions have sufficient human resources, specialized and equipped with technical tools and necessary technology, to have continuous specialized training and to deal with all phenomena of organized crime.